Le Penant et le Dareste face au statut juridique des métis nés de parents inconnus. Une étude comparative (1891-1946) - Silvia Falconieri (Clio@Themis)
In the end of the 19th century, the Recueil Dareste and the Recueil Penant are a part of main French periodicals specialized in colonial law. Through a complete perusal of these two reviews, this contribution aims at realizing a thematic and comparative study by focusing on the problems raised by definition of the legal status of the people been born in ultramarine space of unknown parents. It is a question which occupies the specialists of colonial law from the end of the 19th century. These people must be considered as French citizens or as subject? How Penant and Dareste approached this question? Which are the differences and the interpretative convergences between two reviews? Is it possible to detect two approach in the colonial law?